Differential confocal measurement of microstructure surface topography based on centering error optimization and wavelet threshold denoising. (May 2023) - Huang, Jun; Cui, Yuguo; Liang, Dan; Xiang, Jun; Ying, Ronghui
Highlights: Propose a new topography measurement method to measure the microstructure topography surfaces. Reduce the centering error of 3D topography measurement during the spiral scanning process. Eliminate the noise disturbance on the imaging accuracy of reconstructed topography. The maximum relative error is less than 1.45 % when compared with the commercial microscope, the centering error is within 0.75 μm. Achieve non-contact measurement of microstructure surface topography with high precision and efficiency. Abstract: This paper proposes a precise differential confocal measurement method based on centering error optimization and wavelet threshold denoising (DCM-COWD), which can realize non-contact measurement of microstructure surface topography with high precision and efficiency. Firstly, the influence of pinhole diaphragm size and offset on axial response curve is analyzed through multiple experiments to obtain the optimal pinhole diaphragm diameter and offset of the differential confocal measurement system. Secondly, a probe centering method based on grating rotation successive approximation is designed, in order to reduce the centering error of 3D topography measurement during the spiral scanning process. Thirdly, a translation invariant (TI) wavelet threshold denoising algorithm based on median filtering and whale optimization (WOA) is proposed, which can improve the signal-to-noise ratio (SNR) and reduce the root mean square error (RMSE), and effectively suppress the Pseudo-Gibbs phenomenon of discontinuous points. Finally, the surface topography of a standard sample is measured based on DCM-COWD system. The measurement results show that the center error is within 0.75 μm and the maximum deviation is within 1.45 %. The measurement results show high accordance with the commercial white light interferometer, and the processing speed is improved by 4.17 times. The proposed method has great application potential for the precise and efficient measurement of 3D surface topography.